23 A qualitative study of the perceptions of low carbohydrate diets and their discussion on social media among dietitians in England. (12th April 2022) - Bradfield, James; Butler, Tom; Skinner, Rob; Ray, Sumantra
Abstract : Background: Low carbohydrate diets (LCDs) have gained popularity among those seeking to lose weight and improve glycaemic control. They feature heavily in online discussions such as on social media. Evidence exists to support their use, 1 but at present no universal definition of 'low carbohydrate' exists. Though the practices of dietitians around LCDs have been examined, 2 3 none have assessed this in relation to use of social media. Objectives: The objective was to establish what a representative sample of dietitians in England believe, think and do with LCDs in their clinical practice. Methods: Recruitment of 10 dietitians working in weight management and/or diabetes in England took place online. They completed a short survey and a one-to-one, semi-structured interview using online teleconferencing. Interviews lasted 30 minutes and explored their knowledge, attitudes and practices towards LCDs, and how they are discussed online. Interviews were transcribed for content and thematic analysis. Results: A number of themes became apparent, namely: (1) patient-centred care, (2) LCD community, (3) considered use of LCDs, (4) social media and (5) terminology. Each also had a number of sub-themes, such as individualisation, lack of dialogue and labelling of diets for the themes above. Discussion: Overall, the dietitians in this study were happy to use LCDs with their patients, in a safe and individualised manner. They expressed concerns about how the diets are sometimes represented online as a panacea and the inability to engage in respectful discussion with some of its proponents. These findings add to existing work completed in the area. 2 3 Conclusions: The dietitians in this study were happy to support patients to follow an LCD, in a safe and individualised manner such as under dietetic supervision. They considered them more useful for improving GC and medication reductions. A standard definition of LCDs would help patients and practitioners to communicate effectively. Additionally, education in online engagement could help improve dietitians overall confidence and practice in operating effectively in this environment. References: Hallberg S, McKenzie A, Williams P, et al. Effectiveness and safety of a novel care model for the management of type 2 diabetes at 1 year: an open-label, non-randomized, controlled study. Diabetes Therapy 2018;9 (2):613–621. Huntriss R, Boocock R, McArdle P. Dietary carbohydrate restriction as a management strategy for adults with type 2 diabetes: exploring the opinions of dietitians. Journal of Diabetes Nursing 2019;23 :JDN104. McArdle P, Greenfield S, Avery, et al. Dietitians' practice in giving carbohydrate advice in the management of type 2 diabetes: a mixed methods study. Journal of Human Nutrition and Dietetics 2016;30 (3):385–393.